KESADARAN KEAKRABAN DALAM KELUARGA DAN IMPLIKASINYA TERHADAP KONSELING KELUARGA - Harwansyah Putra Sinaga; Ika Purnamasari (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2019)
The purpose of this study was to obtain a description of the level of awareness of familiarity in the family and its implications for family counseling for students at Al Hafidz Leuwiliang Vocational School. The research design used in this study is a survey design. The instrument used in this study was the Psychological Scale of Familiarity Awareness in the Family. The population in this study were all students of Al Hafidz Leuwiliang Vocational School while the samples used were 115 students with purposive sampling technique. The results of this study indicate that 64 (55.7%) students are in the high category, and 51 (44.3%) students are in the moderate category, and no student (0%) is in the low category. This means students agree that familiarity in the family is an important part of life that must be applied to everyday life at home. Meanwhile, familial awareness is a cognitive aspect that needs to be displayed in the psychomotor (behavior) aspect. So that school counselors can design guidance and counseling programs and activities in schools, especially family counseling programs and services such as the use of parental consultation services to support the goals of family counseling, procurement of parenting activities at school, and integration of family field themes in each services towards students